Richard und die Rahmen zur Rolle von Figurenbüchern für die Konzeption des Prachtchorbuchs Mus.Hs. 2129 der Österreichischen Nationalbibliothek - Lodes, Birgit 1967- (2021)
"The luxury choirbook Vienna, Austrian National Library, Mus.Hs. 2129, created for the Munich wedding celebrations of 1568 between the Bavarian Duke Wilhelm V and Renata of Lorraine, is a veritable Gesamtkunstwerk: it contains the epithalamium Gratia sola Dei by Nikolaus Stopius set to music by Orlando di Lasso, and decorated with hundreds of pen drawings by Richard of Genoa. The present article argues that the layout of this exceptional manuscript is determined first and foremost by the frames, and not by the musical notation contained within the frames. Framing devices of various kinds – whether in the inscriptional zones of the miniatures, as figurative borders of the principal miniatures, or as fixed U-shaped borders around the block of music and text – skilfully and effectively stage the various contents. Richard’s work draws on contemporary picture books (so-called Figurenbände) such as Neuwe biblische Figuren (Frankfurt 1565) by Johann Bocksberger and Jost Amman, and an illustrated edition of Ovid’s Metamorphoses (Frankfurt 1563) – designed by Virgil Solis and narrated in verses by Johannes Posthius – from which he borrows textual additions, figurative illustrations, and decorative borders. He does so not merely in a traditional (iconographical, formal, and decorative) way, but also on a discursive level, in reliance on the pictura-poesis tradition: remarkably, as a marginal device, his frames even the passepartouts copied from the 1563 Ovid edition interact meaningfully with the central images. Finally, this essay suggests that both the models used and the monochrome manner of the execution suggest a connection to Archduke Ferdinand II of the Tyrol."
Zusammenfassung in englischer Sprache
Keywords: Richart; Ferdinand -- II. -- Österreich, Erzherzog -- 1529-1595; Wilhelm -- V. -- Bayern, Herzog -- 1548-1626; Renata -- Bayern, Herzogin -- 1544-1602; Bordüre; Hochzeit; Federzeichnung; Chorbuch; Buchmalerei; Rahmen